Pengaruh PSAK 50/55 (Revisi 2014) Berbasis IFRS dan Kualitas Audit Terhadap Manajemen Laba - Nazarudin, Nazarudin; Suseno, Joko (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
The aim of this study is to analyze the effect of the implementation of the IFRS-based PSAK 50 and 55 (revised 2014) and the audit quality of earning management. Both independent variables, the implementation of IFRS-based PSAK 50/55 (Revised 2014) and the audit quality, are dummy variables. In this study, to measure the earning management this research using revenue discretionary model calculated by using conditional revenue model introduced by Stubben (2010). The sample is secondary data derived from annual financial statements at manufacturing companies listing on Indonesia Stock Exchange (BEI) in 2014-2015. The sample has been taken by purposive sampling method that follow the population criteria. The population are the manufacturing companies by 97 companies for 2 years (2014-2015) as sample. The statistical analysis have been used are multiple linear regression and t-test different test. The findings show that both the implementation of the IFRS-based PSAK 50/55 (Revised 2014) and the audit quality have had a significantly and negatively effect on the earning management practices.